2016
DOI: 10.1111/age.12428
|View full text |Cite
|
Sign up to set email alerts
|

Expression of key glycosphingolipid biosynthesis-globo series pathway genes inEscherichia coliF18-resistant andEscherichia coliF18-sensitive piglets

Abstract: A pioneering study showed that the glycosphingolipid biosynthesis-globo series pathway genes (FUT1, FUT2, ST3GAL1, HEXA, HEXB, B3GALNT1 and NAGA) may play an important regulatory role in resistance to Escherichia coli F18 in piglets. Therefore, we analysed differential gene expression in 11 tissues of two populations of piglets sensitive and resistant respectively to E. coli F18 and the correlation of differential gene expression in duodenal and jejunal tissues. We found that the mRNA expression of the seven g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The P1 antigen and blood group H type 2 antigens were 13.2 (1.0) and 10.9 (0.7) to 12.7 (1.3) in IgM, respectively, but the signal intensity toward high-mannose carbohydrates were negative. The comparison of ganglio- (Table 3) 32,[36][37][38][40][41][42] and globo-series (Table 4) 34,35,[43][44][45] glycolipid signal intensity in naïve monkeys suggested that certain carbohydrates in upstream of the cascades (GA1, GA2, GM2, GD3, or Gb3) showed higher signals than others (Figure 3). In the hierarchical clustering ( Figure 2), GM2 was clustered with GD3 in IgM, and with GD3 and GD2 in IgG.…”
Section: Antibody Signals Toward Non-α-gal Pig Antigens and Its Anamentioning
confidence: 99%
“…The P1 antigen and blood group H type 2 antigens were 13.2 (1.0) and 10.9 (0.7) to 12.7 (1.3) in IgM, respectively, but the signal intensity toward high-mannose carbohydrates were negative. The comparison of ganglio- (Table 3) 32,[36][37][38][40][41][42] and globo-series (Table 4) 34,35,[43][44][45] glycolipid signal intensity in naïve monkeys suggested that certain carbohydrates in upstream of the cascades (GA1, GA2, GM2, GD3, or Gb3) showed higher signals than others (Figure 3). In the hierarchical clustering ( Figure 2), GM2 was clustered with GD3 in IgM, and with GD3 and GD2 in IgG.…”
Section: Antibody Signals Toward Non-α-gal Pig Antigens and Its Anamentioning
confidence: 99%
“…The GAPDH and β-actin genes were used as internal references. The primers for GAPDH were: forward 5'-ACATCATCCCTGCTTC-TACTGG-3', reverse 5'-CTCGGACGCCTGCTTCAC-3'; those for β-actin were: forward 5'-TGGCGCCCAGCAC-GATGAAG-3', reverse 5'-GATGGAGGGGCCGGACTCG-3' (Dong et al, 2016). Each sample was analyzed in triplicate, and relative gene expression was calculated using the 2 -ΔΔCt method (Livak and Schmittgen, 2001).…”
Section: Animals and Sample Collectionmentioning
confidence: 99%
“…Furthermore, these DEGs were enriched in 20 pathways, including 41 significantly enriched Toll-like receptor signaling pathways (i.e., p < 0.05) (see Supplementary Table S3 ). Among them, the pathway of the “Glycosphingolipid biosynthesis-lacto and neolacto series” (ko00940) was enriched in the shFUT8 and shNC samples ( Figure 4 D), which probably played an important role in the regulation of E. coli F18 receptor formation [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we found that FUT8 also significantly affected the glycosphingolipid biosynthesis pathways. Studies showed that glycosphingolipid biosynthesis correlated with the generation of the receptor for E. coli F18 [ 19 , 20 ]. Thus, we speculated that FUT8 most likely regulated E. coli F18 susceptibility via the activation or suppression of TLR signaling (which is related to immune response) and glycosphingolipid biosynthesis (which is related to the formation of the E. coli F18 receptor).…”
Section: Discussionmentioning
confidence: 99%